The Role of Health Education and Healthcare Providers in Promoting Infant Vaccination Perspectives from New Mothers at the Cibiru Vaccine Home - Riza Arlinda (Journal of Healthcare and Biomedical Science, 2025)
Completeness of basic immunizations for infants remains a public health challenge in Indonesia, with various factors such as maternal lack of knowledge, fear of side effects, and misconceptions about vaccines contributing to low coverage rates. This qualitative study aims to explore the perceptions, experiences, and decision-making processes of new mothers regarding infant vaccination at the Cibiru Vaccine Center in Bandung. Data were collected through in-depth interviews with10 motherswho have a baby aged0–12 months,selected using purposive sampling.The interviews explored knowledge of vaccine-preventable diseases, understanding of immunization schedules, perceived benefits, barriers, and the role of health care providers in supporting vaccination decisions.. The data was analyzed thematically, revealing three main themes: (1)Mothers' awareness of the benefits of immunization is often influenced by mothers' knowledge of child health, peer discussions, and direct counseling from health service staff; (2) barriers include fear of post-vaccination side effects, conflicting information from social networks, and logistical challenges such as scheduling and transportation; and (3) trust in health workers at the Cibiru Vaccine House plays an important role in increasing mothers' confidence to complete the immunization schedule.These findings highlight the need for sustained, culturally sensitive health promotion and community engagement to address misconceptions and reinforce the importance of timely and complete infant immunization. Strengthening communication between mothers and health workers at the Cibiru Vaccine Center is crucial to ensure optimal immunization coverage and contribute to reducing preventable infant morbidity and mortality.